The Effect of Season and Meteorological Conditions on Parasite Infection in Farm-Maintained Mouflons (Ovis aries Musimon) - B. Pilarczyk; A. Tomza-Marciniak; R. Pilarczyk; N. Sadowska; J. Udała; J. Kuba (Journal of Parasitology Research)
Due to their limited environment, farm animals are at greater risk of parasitic infection than free-living animals, which also have greater natural resistance to parasitic diseases. The aim of the present study was to determine the influence of season and meteorological conditions (temperature and humidity) on the species composition and dynamics of parasitic infections in farmed mouflons. The study was conducted in a herd of mouflon (n=40) in an extensive system: the animals remained on pasture all year round. The herd was dewormed twice per year with albendazole. Fecal samples were collected at monthly intervals over three years and tested. The prevalence of infection was defined based on coproscopic methods. For most of the studied protozoans (except for E. parva), a greater prevalence was recorded in spring and summer (i.w. from May to September). Regarding nematodes, Capillaria spp., Nematodirus sp., and the Trichostrongylidae demonstrated a much greater prevalence in winter (i.e., in January and December). Temperature and precipitation were found to be positively correlated with intensity of infection by protozoans. However, maximum air temperature was negatively correlated with infection intensity by some nematodes. The deworming practice used in the herd (selection of substance, date, and method of dosing) did not effectively protect the mouflons against parasitoses. Changes in the microclimate resulted in high extent and intensity of mouflon infection with gastrointestinal parasites. Understanding the dynamics of parasitic infections in mouflons during the year allows the development of an appropriate preventive programme.